2018
DOI: 10.1038/s41467-018-03627-9
|View full text |Cite
|
Sign up to set email alerts
|

HSP27 is a partner of JAK2-STAT5 and a potential therapeutic target in myelofibrosis

Abstract: Heat shock protein 27 (HSP27/HSPB1) is a stress-inducible chaperone that facilitates cancer development by its proliferative and anti-apoptotic functions. The OGX-427 antisense oligonucleotide against HSP27 has been reported to be beneficial against idiopathic pulmonary fibrosis. Here we show that OGX-427 is effective in two murine models of thrombopoietin- and JAKV617F-induced myelofibrosis. OGX-427 limits disease progression and is associated with a reduction in spleen weight, in megakaryocyte expansion and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…Besides recognizing pathogens, TLR2 and TLR4 can also be stimulated by diverse endogenous ligands and thereby participate in thromboinflammatory reactions that take place in clinical conditions characterized by sterile inflammation, thus contributing to vascular disease (25). Previous findings from our group and others have revealed the presence of host-derived TLR ligands in MPN, including histone/DNA complexes (26), Hsp27 (27) and EDA-fibronectin (28), which engage TLR2 and/or TLR4. In order to determine the potential contribution of TLRs to platelet activation in ET, we assessed TLR2-and TLR4-mediated platelet thromboinflammatory responses, using the synthetic lipopeptide Pam3CSK4 and LPS, as prototypical TLR2/1 and TLR4 ligands, respectively, and employed classic hemostatic agonists, such as TRAP-6 and thrombin, for comparison.…”
Section: Introductionmentioning
confidence: 93%
“…Besides recognizing pathogens, TLR2 and TLR4 can also be stimulated by diverse endogenous ligands and thereby participate in thromboinflammatory reactions that take place in clinical conditions characterized by sterile inflammation, thus contributing to vascular disease (25). Previous findings from our group and others have revealed the presence of host-derived TLR ligands in MPN, including histone/DNA complexes (26), Hsp27 (27) and EDA-fibronectin (28), which engage TLR2 and/or TLR4. In order to determine the potential contribution of TLRs to platelet activation in ET, we assessed TLR2-and TLR4-mediated platelet thromboinflammatory responses, using the synthetic lipopeptide Pam3CSK4 and LPS, as prototypical TLR2/1 and TLR4 ligands, respectively, and employed classic hemostatic agonists, such as TRAP-6 and thrombin, for comparison.…”
Section: Introductionmentioning
confidence: 93%
“…Upstream from STAT3/5 activation, JAK2 plays a major role that can be modulated by HSP27 [141]. In the specific context of thrombopoietin-and JAK2 V617F -induced myelofibrosis (a chronic degenerative disorder of the hematopoietic system associated with the aberrant activation of the JAK/STAT pathway) [142], our team has recently shown that HSP27 interacts directly with JAK2/STAT5, stabilizing the complex.…”
Section: Hsp27 Functionsmentioning
confidence: 99%
“…Nucleic acids. Built from a selection of four natural building blocks (G, C, A, T/U) and additional artificial ones, DNA/RNA sequences operate either by interfering with gene expression, e.g., antisense oligonucleotides [50][51][52] and RNAi [53][54][55] , or through their unique folding geometry, which allows them to interact structurally with a target molecule, e.g., aptamers 41,56-60 and ribozymes [61][62][63] . While not widespread at this point, these short DNA-sequences have already proven their potential efficacy, for example inhibiting the activity of human immunodeficiency virus (HIV) 64,65 , as well as other applications at various stages of clinical trials 58 .…”
Section: Box I Digitizable Therapeuticsmentioning
confidence: 99%